The collection of Test Tasks on hospital pediatrics for the 5 th year English-speaking students of medical faculty "Neonatology". - Lezhenko, G. O.; Reznichenko, Yu. G.; Pashkova, O. E.; Hyria, O. M.; Kamenshchyk, A. V.; Lebedinets, O. M.; Gladun, K. V.; Sidorova, I. V.; Леженко, Геннадій Олександрович; Резніченко, Юрій Григорович; Пашкова, Олена Єгорівна; Гиря, Олена Максимівна; et al. (ЗДМУ, 2016)
During the hospital pediatrics course for students who studying on “General Medicine” specialty there are 10 lectures wil bel delivered ( 20 educational hours), and 15 four sentinel practical classes (60 educational hours) will be conducted, 40 educational hours will be selected for independent outclass students work. During the study there are 2 final intermediate class and the case history passing is conducted that is the students have to write by the diseases of new-born children. In completion of studying course the students pass 2 module tests from the subject of “hospital pediatrics”. In 9-10 semesters the students of “General Medicine” specialty study the diseases of new-born children, of endocrine and blood systems. Teaching of treatment questions is conducted differently for outpatient and hospital stages, for the stages of rehabilitation and clinical supervision.
Keywords: neonatology; test tasks; hospital pediatrics; students